Listado taxonómico de los asteroideos (Echinodermata: Asteroidea) de la plataforma y el talud superior del Caribe colombiano - Benavides-Serrato, Milena (2005)
Taxonomic list of the asteroids (Echinodermata: Asteroidea) from the shelf and superior slope from the Colombian Caribbean. Between 1998 and 2001 we surveyed the benthic macrofauna of the continental shelf and its upper slope in the Colombian Caribbean. The INVEMAR-MACROFAUNA I-II expeditions used a “semi-ballon” net were for 10 minutes bottom drags from Punta Gallinas (Guajira) to Arboletes (Antioquia). These covered seven ecological sectors from the Colombian Caribbean: Guajira (GUA), Palomino (PAL), Tayrona (TAY), Magdalena (MAG), Archipiélagos Coralinos (ARCO), Morrosquillo (MOR), and Darién (DAR). We collected 4109 Asteroidea individuals belonging to six orders, 13 families, 26 genera, four subgenera, 35 species and eight subspecies. Luidia barbadensis, Luidia heterozona barimae, Luidia ludwigi scotti, Luidia sarsi elegans, Prionaster elegans, Cheiraster (Cheiraster) planus, Cheiraster (Cheiraster) sepitus, Cheiraster (Barbadosaster) echinulatus, Pseudarchaster gracilis gracilis, Rosaster alexandri, Pteraster acicula, Pteraster militarioides militarioides, Doraster constellatus, Mammaster sigsbeei and Coronaster briareus are first records for the Colombian Caribbean. Luidia sarsi elegans, Marginaster pectinatus, Tamaria halperni and Stephanasterias albula are first records for the south Caribbean and Pteraster personatus and Dipsacaster antillensis are first records for the Caribbean sea. Rev. Biol. Trop. 53(Suppl. 3): 171-194. Epub 2006 Jan 30.